PERAN PEGADAIAN SEBAGAI LEMBAGA KEUANGAN TERHADAP MASYARAKAT MIKRO - Ivan Fadilla Hadi, Ivan (2021)
Universal changes in Indonesia at this time often experience a crisis, especially in the economic sector. The current pandemic era shows some difficulties for Micro, Small and Medium Enterprises in running a business. The condition of MSMEs is increasingly difficult to compete with large companies, because MSMEs are a pillar of the economy for the lower middle class. Therefore, PT Pegadaian (Persero) has proven to be one of the non-bank financial institutions that helps the community in running Micro, Small and Medium Enterprises. PT Pegadaian (Persero) shows its role as an example of a financial institution in Indonesia in an effort to support MSMEs, aiming to be able to control and support state activities in the national formation economic sector. This is the background for the author to determine the role of PT Pegadaian (Persero) as a non-bank financial institution for the micro community. This final project was prepared with the aim of knowing the implementation in increasing satisfaction and providing solutions to the community. Based on data processing, the role of PT Pegadian (Persero) is very important, because it can help the economy of people who need funds for their lives.